Precision medicine ethics: selected issues and developments in next-generation sequencing, clinical oncology, and ethics. Issue 1 (January 2016) - Fiore, Robin N.; Goodman, Kenneth W.
Abstract : Purpose of review: In early 2015 the National Institutes of Health launched a new, national Precision Medicine Initiative with the primary goal of rapidly improving the prevention, diagnosis, and treatment of cancers. The first-stage emphasis on oncology presents unique opportunities for clinical oncology to influence how the ethical challenges of precision medicine are to be articulated and addressed. Thus, a review of recent developments in connection with the Initiative, in particular on core ethics issues in clinical genomics, is a useful starting point. Recent findings: Unique ethical issues arise in precision medicine because of the enormous amounts of data generated by clinical whole-genome or whole-exome sequencing and the extent of current uncertainties with respect to data interpretations and disease associations. Among the most ethically challenging issues for clinicians are complicated informed consent processes, returning results – particularly secondary and incidental findings–and privacy and confidentiality. Summary: The first tests of precision medicine ethics in practice will be in clinical oncology, providing a rare opportunity to shape the agenda and integrate practical ethics considerations. These efforts can benefit from pre-existing research ethics analyses and recommendations from clinical and translational genetics research.